ANALISIS KEKUATAN IMPACT BAHAN MIXER BLADE AKIBAT PENGARUH HEAT TREATMENT - Ihya Sulaiman, Muhamad Yusril; Hamdani, R. Aam; Wardaya; Komaro, Mumu (Universitas Nusa Putra, 2021)
Mixer blade is one of the tools used in the cement industry as a tool to mix the composition of raw cement into ready-to-use cement. However, in its use, damage is often caused when the mixing process takes place, there is material that is too hard and makes the blade break. Based on these problems, the author made a study entitled